Estudo visando a aplicação de caulim duro como matéria-prima para obtenção de micas sintéticas - SERRÃO, Fernanda Thamiles de Jesus (2019)
Brazil is a reference in kaolin production, especially in the Amazon region with emphasis on Pará, Amapá and Amazonas. High production results in a significant amount of industrial waste, which without proper disposal can cause social and environmental problems. Recently, studies are being developed for the use of industrial waste as a starting material in the synthesis of nanostructured materials. Therefore, the study of nanometric materials has gained significant importance, among them the alumicasilicates of the mica group, the study of these particulate materials has properties linked to the process and the conditions of synthesis. This work aims to use kaolin flint, considered as sterile and unviable for the paper industry, evaluating the possibility of its use as raw material in the synthesis of type 2: 1 phylosilicates from the mica group. Starting material and phases formed as reaction product were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and infrared spectroscopy (FTIR). Synthesis reactions were carried out by hydrothermal method, with the reaction gel composed of: kaolin flint in natura/kaolin flint calcined, potassium hydroxide and manganese nitrate, using autoclaves at 150 ° C and 160 ° C in 24 and 48 hours. The results demonstrate that with the developed methodology it is possible to obtain micaceous clay minerals within the studied conditions of time and temperature, and that the time and temperature of synthesis have influence on the degree of crystallinity of the material.